THE INFLUENCE OF COMMUNICATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE VOCATIONAL AND PRODUCTIVITY TRAINING CENTER (BBPVP) MEDAN - Stevani Oktaviani Pandiangan; Khairunnisak; Wan Rizca Amelia; Irwansyah Putra; Teddi Pribadi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study was to analyze the effect of communication and employee work environment at the Vocational and Productivity Training Center (BBPVP) Medan. The population in this study was 120 sourced from data from the Vocational and Productivity Training Center (BBPVP) Medan, with a sample of 93 respondents determined by the Slovin formula. This type of research is quantitative. With the sampling method used is proportional random sampling. The results showed that communication had a positive and significant effect on the performance of employees of the Vocational and Productivity Training Center (BBPVP) Medan, the work environment had a positive and significant effect on the performance of employees of the Vocational and Productivity Training Center (BBPVP) Medan.